Identification of a polycystin-1 cleavage product, P100, that regulates store operated Ca entry through interactions with STIM1. - Owen M Woodward; Yun Li; Shengqiang Yu; Patrick Greenwell; Claas Wodarczyk; Alessandra Boletta; William B Guggino; Feng Qian (PLoS ONE)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a genetic disorder resulting in large kidney cysts and eventual kidney failure. Mutations in either the PKD1 or PKD2/TRPP2 genes and their respective protein products, polycystin-1 (PC1) and polycystin-2 (PC2) result in ADPKD. PC2 is known to function as a non-selective cation channel, but PC1's function and the function of PC1 cleavage products are not well understood. Here we identify an endogenous PC1 cleavage product, P100, a 100 kDa fragment found in both wild type and epitope tagged PKD1 knock-in mice. Expression of full length human PC1 (FL PC1) and the resulting P100 and C-Terminal Fragment (CTF) cleavage products in both MDCK and CHO cells significantly reduces the store operated Ca(2+) entry (SOCE) resulting from thapsigargin induced store depletion. Exploration into the roles of P100 and CTF in SOCE inhibition reveal that P100, when expressed in Xenopus laevis oocytes, directly inhibits the SOCE currents but CTF does not, nor does P100 when containing the disease causing R4227X mutation. Interestingly, we also found that in PC1 expressing MDCK cells, translocation of the ER Ca(2+) sensor protein STIM1 to the cell periphery was significantly altered. In addition, P100 Co-immunoprecipitates with STIM1 but CTF does not. The expression of P100 in CHO cells recapitulates the STIM1 translocation inhibition seen with FL PC1. These data describe a novel polycystin-1 cleavage product, P100, which functions to reduce SOCE via direct inhibition of STIM1 translocation; a function with consequences for ADPKD.